2008
DOI: 10.1074/jbc.m804753200
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the cIAP2 RING Domain Reveal Conformational Changes Associated with Ubiquitin-conjugating Enzyme (E2) Recruitment

Abstract: Inhibitor of apoptosis (IAP) proteins are key negative regulators of cell death that are highly expressed in many cancers. Cell death caused by antagonists that bind to IAP proteins is associated with their ubiquitylation and degradation. The RING domain at the C terminus of IAP proteins is pivotal. Here we report the crystal structures of the cIAP2 RING domain homodimer alone, and bound to the ubiquitin-conjugating (E2) enzyme UbcH5b. These structures show that small changes in the RING domain accompany E2 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
166
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 32 publications
16
166
0
Order By: Relevance
“…1C). This surface, comprising residues on the N-terminal helix (H1), loop 4, and loop 7 (L4 and L7), is the canonical E3 interaction surface through which UbcH7 interacts with both HECT and RING E3 ligases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). A highly conserved phenylalanine residue in L4 (F63 in UbcH7) seems to be the determinant for HECT E3 recognition.…”
Section: Resultsmentioning
confidence: 99%
“…1C). This surface, comprising residues on the N-terminal helix (H1), loop 4, and loop 7 (L4 and L7), is the canonical E3 interaction surface through which UbcH7 interacts with both HECT and RING E3 ligases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). A highly conserved phenylalanine residue in L4 (F63 in UbcH7) seems to be the determinant for HECT E3 recognition.…”
Section: Resultsmentioning
confidence: 99%
“…A highly conserved Phe is represented in green stick format. Coordinates are from Dueber and colleagues (Dueber et al 2011), PDB: 3T6P, and Mace and colleagues (Mace et al 2008) (Komander and Rape 2012). Whether ubiquitylation targets proteins for degradation or mediates nondegradative signaling depends on protein interactions between the ubiquitylated protein and Ub-binding proteins, which can therefore be considered as Ub "receptors" (Hoeller et al 2006).…”
Section: Ring Fingermentioning
confidence: 99%
“…cIAP1's E3 ligase activity can be activated following binding to a substrate. Substrate-binding to the BIR3 liberates the RING from BIR3-mediated inhibition, exposing two interaction surfaces required for RING dimerization and E2 binding, respectively (Mace et al 2008). RING dimerization is of particular importance as it is indispensable for the transfer of Ub from the E2 to a lysine residue of the target substrate.…”
Section: Iaps As Modulators Of Cell Death and Inflammationmentioning
confidence: 99%
“…Our previous structural studies showed that the RING domain of cIAP2 exists as a dimer and that the dimer bound directly to the E2 UbcH5b (20). To understand how IAP antagonists promote autoubiquitylation of cIAPs, we focused on identifying the essential features of the RING domain.…”
mentioning
confidence: 99%
“…Some IAPs, such as X-linked IAP, can directly inhibit caspases and prevent proteolytic cleavage, whereas cIAP1 and cIAP2 are recruited to tumor necrosis factor (TNF) receptor complexes (16) and modulate the receptor-mediated apoptotic pathways that lead to NF-B activation (17,18). The C-terminal RING domains of cIAP1 and cIAP2 are critical (19,20) with the RING domain required for dimerization, substrate ubiquitylation, and autoubiquitylation (21)(22)(23). In addition to the RING domain, all IAPs have N-terminal baculoviral IAP repeat (BIR) domains that can bind to other proteins, such as the IAP antagonist Smac/DIABLO (second mitochondrion-derived activator of caspase or direct IAP-binding protein with low pl) (24,25).…”
mentioning
confidence: 99%